Contribution of Time of Drinking Onset and Family History of Alcohol Problems in Alcohol and Drug Use Behaviors in Argentinean College Students - Pilatti, Angelina (2014)
Aims: The aim of the study was to analyze independent and potential interactive effects of age at drinking onset and family history of alcohol abuse on subsequent patterns of alcohol drinking, alcohol-related problems and substance use. Methods: Participants were college students (60.3% females, mean age = 20.27 ± 2.54 years) from the city of Córdoba, Argentina. Several measures were used to assess alcohol, tobacco and drug use. The Spanish version of the Brief Young Adult Alcohol Consequences Questionnaire was used to assess alcohol-related problems. Factorial analyses of variance, or its non-parametric equivalent, were performed to explore differences in substance use behaviors and alcohol-related problems in subjects with early or late drinking onset and with or without family history of alcohol abuse. Chi-square tests were conducted to analyze the association between these two risk factors and categorical measures of alcohol, tobacco and drug use. Results: Early onset of drinking was associated with amount of consumption of alcohol including up to hazardous levels, as well as tobacco and drug use. However, the frequency of alcohol problems and frequency of episodes of alcohol intoxication were only related to age of onset in those with a positive family history of alcohol problems. Conclusion: Delaying drinking debut is particularly important in the prevention of future alcohol problems in those adolescents who have a family history of such problems.